The pharmacogenomics of severe traumatic brain injury. (October 2017) - Adams, Solomon M; Conley, Yvette P; Wagner, Amy K; Jha, Ruchira M; Clark, Robert SB; Poloyac, Samuel M; Kochanek, Patrick M; Empey, Philip E
Pharmacotherapy for traumatic brain injury (TBI) is focused on resuscitation, prevention of secondary injury, rehabilitation and recovery. Pharmacogenomics may play a role in TBI for predicting therapies for sedation, analgesia, seizure prevention, intracranial pressure-directed therapy and neurobehavioral/psychiatric symptoms. Research into genetic predictors of outcomes and susceptibility to complications may also help clinicians to tailor therapeutics for high-risk individuals. Additionally, the expanding use of genomics in the drug development pipeline has provided insight to novel investigational and repurposed medications that may be useful in the treatment of TBI and its complications. Genomics in the context of treatment and prognostication for patients with TBI is a promising area for clinical progress of pharmacogenomics.